SMART PROXY MODELING artificial intelligence and machine learning in numerical simulation. - Mohaghegh, Shahab D. ([S.l.] : CRC PRESS, 2023)
Numerical simulation models are used in all engineering disciplines for modeling physical phenomena to learn how the phenomena work, and to identify problems and optimize behavior. Smart Proxy Models provide an opportunity to replicate numerical simulations with very high accuracy and can be run on a laptop within a few minutes, thereby simplifying the use of complex numerical simulations, which can otherwise take tens of hours. This book focuses on Smart Proxy Modeling and provides readers with all the essential details on how to develop Smart Proxy Models using Artificial Intelligence and Machine Learning, as well as how it may be used in real-world cases. Covers replication of highly accurate numerical simulations using Artificial Intelligence and Machine Learning Details application in reservoir simulation and modeling and computational fluid dynamics Includes real case studies based on commercially available simulators Smart Proxy Modeling is ideal for petroleum, chemical, environmental, and mechanical engineers, as well as statisticians and others working with applications of data-driven analytics.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Artificial Intelligence; TECHNOLOGY / Petroleum; TECHNOLOGY / Engineering / Chemical & Biochemical; Engineering models -- Data processing; Engineering -- Data processing; Computer simulation; Mathematical models; Artificial intelligence; Machine learining; Numerical analysis